2011
DOI: 10.4236/jwarp.2011.33021
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Global Issue of Rising Water Scarcity for Agriculture: The Quest for Effective and Feasible Soil Moisture and Free-Water Surface Conservation Strategies

Abstract: There is the need to take seriously the task of conserving soil moisture in agricultural fields and free-water surfaces in reservoirs, especially in recent years of climate change. Many strategies exist for achieving this task and improving the productivity of arable soils. These strategies traditionally come under biological and physical or mechanical measures. Some other relatively new techniques operate neither on physical nor on biological principle. All these measures which operate on different principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…The many benefits of surface mulch to the soil and the crop grown therein are well known, including maintenance of uniformly high soil water status thus reducing irrigation frequency especially in dry season production (Obalum et al. ). Odiaka et al.…”
Section: Introductionmentioning
confidence: 99%
“…The many benefits of surface mulch to the soil and the crop grown therein are well known, including maintenance of uniformly high soil water status thus reducing irrigation frequency especially in dry season production (Obalum et al. ). Odiaka et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, water availability to crop roots in the soil profile constitutes a major constraint for sustainable production systems [14][15][16][17]. Because of unpredictable rainfall [18] and decreased agricultural productivity, many soil and water conservation technologies such as stone lines, half-moons, contour hedgerows, rock bunds, filter walls, zaï, agroforestry, contour ridges, benches and no-tillage have been developed and are now widespread [19][20][21][22][23]. Tested technologies have shown that they can reduce runoff [16,[24][25][26] and soil erosion [27][28][29], improve water infiltration [12,22,30] and increase soil moisture [20,23,[31][32][33].…”
Section: Open Accessmentioning
confidence: 99%
“…Palm trees offer the much-needed protection to the soil and the entire environment by at least two mechanisms; (i) ability of the closed tree canopy to intercept the usually high-intensity rainfall, thereby reducing its erosive power upon reaching the ground, and (ii) enhanced structural-hydraulic properties of soils. This implies increased rainwater infiltration/retention in the soil, such that palm trees serve as a biological measure of agricultural water conservation (Obalum et al, 2011). Regarding the required improvements in soil structural-hydraulic properties, oil palm plantation has severally been reported to be superior to arable cropping in southeastern Nigeria (Igwe, 2001;Ogban, 2017;Uzoma and Onwuka, 2018).…”
Section: Multipurose Roles Of Oil Palm Ecological Benefits Of the Oilmentioning
confidence: 99%